Effect of methanolic extract of Tetrapleura tetraptera (Schum and Thonn) Taub leaves on hyperglycemia and indices of diabetic complications in alloxan-induced diabetic rats - Atawodi, Sunday Ene-Ojo (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To investigate the ameliorative role of Tetrapleura tetraptera (Schum and Thonn) Taub (T. tetraptera) leaf in hyperglycemia with associated conditions like oxidative stress, kidney damage and disorders in lipid metabolism. METHODS: Five groups of five rats each intraperitoneally received the following treatment schedules for 7 d: untreated normal control, untreated alloxan-diabetic control, diabetic treated with glibenclamide, normal rats treated with extract (50 mg/kg) and diabetic rats treated with the extract. Evaluations were made for fasting blood sugar, body weight changes, malondialdehyde, aspartate aminotransferase, alanine aminotransferase, bilirubin, superoxide dismutase, catalase, lipid profile, packed cell volume, hemoglobin, urea and creatinine in all the rats. RESULTS: Whereas the untreated diabetic rats showed a significant decrease (P<0.05) in packed cell volume, superoxide dismutase, catalase and high-density lipoprotein-cholesterol with a concomitant increase in the levels of malondialdehyde, fasting blood sugar, aspartate aminotransferase, alanine aminotransferase, bilirubin, urea and creatinine, administration of methanolic extract of T. tetraptera leaf or glibenclamide alleviated these altered parameters in the treated rats. CONCLUSIONS: Methanolic extract of T. tetraptera leaves possesses a potent capacity for treatment of diabetes and the accompanying complications, including oxidative stress and hyperlipidemia.